Knowledge, attitude and practice study on swine flu (H1N1) among adolescent school children in Kolhapur district in Maharashtra - Yadav, Jeevankumar U.; Shete, Jagannath S. (International Journal Of Community Medicine And Public Health, 2020)
Background: Swine flu (H1N1) is very infectious respiratory disease occurring in different parts of world showing pandemicity from time to time. Thorough knowledge about its epidemiology and clinical symptoms, attitude towards disease and practices to prevent its occurrence and spread are essential in all age groups especially in school children. To assess the awareness, practices, their attitude and myths regarding swine flu among adolescent school going children in Kolhapur district Maharashtra. Methods: A pre-tested questionnaire was designed emphasized on the demographic profile, knowledge and misconceptions about cause, transmission, prevention and cure of swine flu (H1N1) and social responsibility of every student about spreading awareness. The questionnaires were distributed to school students of 9th& 10th standard only. Maximum 15 minutes were allotted to participants. A power point presentation regarding swine flu was delivered to participants and staff members. Results: Total 210 study participants were included. 80.47% students knew cause of swine flu is viral and 69.04% knew it spreads through airborne route. 73.33% students correctly knew about symptoms of swine flu. 71.90% mentioned all the correct preventive methods as wearing face mask of appropriate size, vaccination against swine flu and maintaining hand hygiene. In reality only 32.38% students exclusively practicing hand hygiene. Conclusions: Although the term was well known, better recognition of pandemic influenza cases is needed. Children were not aware about certain important treatment and prevention aspects of the disease.